The mediating role of blood metabolites in the association between myocardial infarction and cancer risk: An observational and mendelian randomization analysis - Jia Zhu; Xiaojun Xia; Haodong Jiang; Congying Wang; Yunpeng Jin (PLoS ONE, 2025)
Background Myocardial infarction (MI) and cancer are major global public health challenges. Research indicates that they share common risk factors and that physiological changes following MI may affect cancer incidence and progression. However, evidence defining the independent relationship between these conditions is still limited. Methods We analyzed data from the National Health and Nutrition Examination Survey (NHANES) (2011–2018) using multivariable weighted logistic regression to examine the association between myocardial infarction (MI) and cancer. Additionally, we utilized genome-wide association study (GWAS) summary statistics and conducted Mendelian randomization (MR) to assess potential causal relationships and explore underlying mechanisms. Sensitivity analyses were performed to ensure the robustness of our findings. Results A total of 20,859 participants were included in our observational study using NHANES data. Multivariable weighted logistic regression revealed no direct association between MI and cancer (OR=1.161, 95% CI [0.895–1.507], P = 0.261). Interestingly, MR analysis indicated that MI occurrence was associated with a reduced incidence of cancer (OR=0.9497, 95% CI [0.9223–0.9778], P = 0.0005). Furthermore, two-stage MR results suggested this reduction might be mediated by increased blood levels of metabolites that inhibit cancer development, such as dihomo-linoleate (20:2n6) (beta = −0.0050, 95% CI [−0.0027–0.0004], P < 0.0001), alpha-tocopherol (beta = −0.0042, 95% CI [−0.0060–0.0025], P < 0.0001), inosine (beta = −0.0015, 95% CI [−0.0027–0.0004], P = 0.0084), and methyl glucopyranoside (alpha + beta) levels (beta = −0.0006, 95% CI [−0.0010–0.0003], P = 0.0008). Conclusion Our integrative analysis suggests that myocardial infarction may be associated with a reduced cancer incidence through potential alterations in blood metabolite profiles, including dihomo-γ-linolenic acid, alpha-tocopherol, and inosine. These findings provide preliminary evidence that warrants further large-scale studies to validate the observed associations and to elucidate the underlying mechanisms.